The Impact of an Exhaustive Exercise on Static Balance of Freestyle Wrestlers with Flat Foot - Ali Roshandel Hesari; Mahdi Sabbagh Langeroudi; Rasool Nazari (Biyumikānīk-i varzishī)
Objective: The purpose of this study was to the impact of an exhaustive exercise on static balance of freestyle wrestlers with flat foot. number of 15 freestyle wrestlers north khorasan province, the method semi-empirical and purposefully based on anthropometric variables with mean and standard deviation, BMI (kg/m2) (25.41±3.619) per square meter, Age (y) (22.8±2.833), Weight (kg) (79.9±1.837), Height (cm) (176.25±8.331) were intrant this studied. Methods: The data analysis from descriptive statistical method (mean and standard deviation) and inferential statistics method (Shapiro-Wilk test dependent t-test was used to evaluate intragroup changes (P≤0.05). Results: The results this research showed, between static balance and wrestlers flat foot after an exhaustive practice a significant relationship and over affinity was between demographic characters with static balance in wrestlers with flat foot (P≤0.05). Conclusion: Based on research results, it can be concluded that flat foot deformity associated with exhaustive exercise can on postural control and affected static balance freestyle wrestlers.